PENGARUH MODERNISASI ADMINISTRASI PERPAJAKAN, PENGETAHUAN PERPAJAKAN, SOSIALISASI PERPAJAKAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI WILAYAH KABUPATEN BEKASI - Melinda Dwi Haryanti; Bayu Seno Pitoyo; Andhika Napitupulu (Jurnal Akuntansi dan Perpajakan Jayakarta, 2022)
The Effect of Tax Administration Modernization, Tax Knowledge, Tax Socialization, and Tax Sanctions on Individual Taxpayer Compliance in the Bekasi Regency Area. This study aims to examine and analyze the effect of tax administration modernization, taxation knowledge, tax socialization, and tax sanctions on individual taxpayer compliance in the Bekasi Regency area. The object of this research is an individual taxpayer with NPWP in Bekasi Regency. This type of research is quantitative research with descriptive approach method. The data collection technique in this study used questionnaires via google form. The sample selection method in this study is a random sampling method. The sample used is 100 individual taxpayers. The method of analysis using multiple linear regression analysis using SPSS version 23 program. Based on the results of the partial study, it shows that administrative modernization has no effect on individual taxpayer compliance. However, tax knowledge, tax socialization and tax sanctions have a positive and significant effect on individual taxpayer compliance. Simultaneously modernization of tax administration, knowledge of taxation, socialization of taxation, and tax sanctions simultaneously affect the compliance of individual taxpayers in the Bekasi Regency area.